An innovative environmental control system of subway. Issue 147 (December 2015) - Yang, Zhao; Su, Xiangchao; Ma, Feng; Yu, Longqing; Wang, Hongna
Abstract: An innovative platform screen doors (PSDs) system with controllable slits was introduced, aiming to improve traditional PSDs and automatic platform gates (APGs) system. A newly-built subway station was used as a prototype to analyze and demonstrate the feasibility and energy savings opportunities of this innovative system. The process of train arrival and departure at a station was studied by transient simulation using computational fluid dynamics (CFDs) method, and the calculation of CFD was validated. Comfort, air ventilation and energy savings achievements in the station from piston wind were analyzed. After analyzing the thermal environment of the station and tunnel and five operation models, a new control scheme was implemented in this paper. Energy savings from the new control scheme used in eight cities were calculated. The results show that the new environmental control system meets comfort requirements. When compared with the traditional PSDs system, energy consumption is reduced by using optimized opening and operating programs. The energy savings of the new control scheme in different cities are remarkable, especially during the "shoulder" months when air conditioning is not available in the system. Graphical abstract: Highlights: We introduce an innovative environmental control system. Simulation results show the innovative environmental control system is feasible. The energy-saving effect of the new system in different cities is different. The experimental data indicates the energy-saving effects are improved.